Investigation of Beta-Lactam and Tetracycline Group Antibiotic Residues in Bovine Liver, Kidney and Muscle Tissue - Sema Ağaoğlu; Nazlı Ercan; Emre Hastaoğlu (Turkish Journal of Agriculture: Food Science and Technology, 2021)
In this study, beta-lactam and tetracycline antibiotic residues were investigated in cattle liver, kidney and muscle samples. For this purpose, a total of 75 bovine tissue samples (each of 25 from liver, kidney, muscle) taken from 25 cattle slaughtered in a local slaughterhouse in Sivas were used as materials. ELISA method was applied in the analysis and it was studied with commercial test kits. According to the results of the analysis; beta-lactam and tetracycline residues were detected in all bovine tissue samples. Beta-lactam level was determined between 0.75-1.07 ppb (mean 0.94 ± 0.01) in liver samples, 0.67-1.05 ppb (mean 0.81 ± 0.01) in kidney samples and 0.70-2.57 ppb (mean 0.97 ± 0.07) in muscle samples. Tetracycline level was detected in the range of 4.48-8.50 ppb (mean 6.14 ± 0.17) in liver samples, 1.73-6.39 ppb (mean 4.90 ± 0.24) in kidney samples and 3.31-7.45 ppb (mean 5.67 ± 0.25) in muscle samples. The residue levels determined in the examples complied with the legal limits reported in the European Commission and the Turkish Food Codex Communiqué.